The Effect of Science Learning Assisted by TikTok Media on Learning Outcomes of Junior High School Students - Makfiroh, Anisatul; Wulandari, Fitria Eka (JURNAL PENDIDIKAN SAINS (JPS), 2024)
Many educators still carry out science learning by using books as the main learning material without using learning media. This affects student learning outcomes. Judging from the results of the acquisition of daily test scores of 8th-grade students at Muhammadiyah 5 Tulangan Junior High School with a percentage of 69% as many as 80 out of 115 students scored below the minimum completeness criteria of 75. Therefore, there is a need for media in science learning. This study aims to determine the effect of TikTok-assisted science learning on the learning outcomes of Junior High School students. The material used is the human digestive system in the 8th grade of Muhammadiyah 5 Tulangan Junior High School. The study used two classes selected by random sampling technique, namely the experimental class using the TikTok application and the control class using PPT. Data collection used pre-test and post-test tests with 25 items covering cognitive aspects C1-C6. The acquisition of the T-test (Independent sample T-Test) sig value of 0.000 indicates a significant effect on learning outcomes. The N-Gain value of both classes is in the medium category, but the experimental class is higher than the control class. The experimental class obtained a value of 0.62 while the control class obtained a value of 0.36. It is concluded that learning science using the TikTok application has a positive effect on the learning outcomes of Junior High School students. However, educators must continue to monitor students.